2014
DOI: 10.4137/cin.s14060
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the Effects of Honokiol on the Notch Signaling Pathway in SW480 Colon Cancer Cells

Abstract: In a tumor cell, the development of acquired therapeutic resistance and the ability to survive in extracellular environments that differ from the primary site are the result of molecular adaptations in potentially highly plastic molecular networks. The accurate prediction of intracellular networks in a tumor remains a difficult problem in cancer informatics. In order to make truly rational patient-driven therapeutic decisions, it will be critical to develop methodologies that can accurately infer the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…In addition, there were reduced levels of DCLK1 and the Notch signalling-related proteins in the xenograft tissues. Together, these data suggest that honokiol is a potent inhibitor of colon cancer growth that targets the stem cells by inhibiting the γ-secretase complex and the Notch signalling pathway [35,204].…”
Section: Notch Signalling Pathwaymentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, there were reduced levels of DCLK1 and the Notch signalling-related proteins in the xenograft tissues. Together, these data suggest that honokiol is a potent inhibitor of colon cancer growth that targets the stem cells by inhibiting the γ-secretase complex and the Notch signalling pathway [35,204].…”
Section: Notch Signalling Pathwaymentioning
confidence: 84%
“…It was shown that honokiol enhanced the sensitization of GBM cells to MGMT inhibitor O6 benzylguanine (O6-BG) through the downregulation of Notch3 as well as the expression of its downstream target, Hes1 [36]. Furthermore, honokiol has been shown to inhibit B16/F-10, SKMEL-28 melanoma cell lines and SW480 colon cancer cells by targeting Notch signalling pathways [203,204]. Honokiol treatment resulted in reduced levels of cleaved Notch, particularly the Notch-2 receptor, along with a decrease in the expression of downstream target proteins, including Hes-1, cyclin D1, as well as TACE and γ-secretase complex proteins in melanoma cells [55].…”
Section: Notch Signalling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…HNK may exerts such activities through various signaling pathways and molecules, such as STAT3, epidermal growth factor receptor (EGFR), nuclear factor-κB (NF-κB), cell survival signaling, cell cycle, and inflammatory mediators (10)(11)(12)(13). It has been reported that HNK shows anticancer activities in CRC (14)(15)(16), but the explicit mechanism under this effect remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wynn and colleagues (19) develop a network model of Notch signaling in colon cancer using a novel reverse engineering Boolean-based method and discover potential mechanisms of actin for honokiol as an anti-cancer drug. Boolean models are also specifically suited to capturing the qualitative features of interacting components, such as T cell receptor signaling, cell cycle transition between the G1/S phases and hepatocellular specification (2023).…”
Section: Introductionmentioning
confidence: 99%